2017
DOI: 10.1108/ijwbr-04-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Wine prestige and experience in enhancing relationship quality and outcomes

Abstract: Methods: wine brand prestige, wine consumer experience, consumer satisfaction, wine brand image, word-of-mouth,, relationship quality Purpose: the purpose of this study is twofold: (i) conduct a systematic literature review on relationship quality; (ii) analyse the effect of wine brand prestige and wine consumer experience on consumer satisfaction, as well as the wine brand image and word-ofmouth as outcomes. Design/methodology/approach: we employ a systematic approach to develop the literature review and a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 82 publications
1
16
0
Order By: Relevance
“…They are striving for ways to understand wine enthusiasts' needs and expectations and market themselves in a manner that can lead to gratification on various value-creation dimensions (Grönroos and Voima, 2013). Vineyards are promoting a lifestyle, societal projection and replication of international holiday patterns (Bruwer et al, 2013;Bruwer, 2003;Loureiro and Cunha, 2017) to gain attention. Although India is relatively in a nascent stage of wine tourism as compared to other countries (Kotur, 2018), it is quickly growing because of its unique approach and promotions that differ from typical Indian tourism (Kansara, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They are striving for ways to understand wine enthusiasts' needs and expectations and market themselves in a manner that can lead to gratification on various value-creation dimensions (Grönroos and Voima, 2013). Vineyards are promoting a lifestyle, societal projection and replication of international holiday patterns (Bruwer et al, 2013;Bruwer, 2003;Loureiro and Cunha, 2017) to gain attention. Although India is relatively in a nascent stage of wine tourism as compared to other countries (Kotur, 2018), it is quickly growing because of its unique approach and promotions that differ from typical Indian tourism (Kansara, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the consumer uses different sources of information to infer which one better suits his preferences and/or quality requirements (Spiller and Belogolova, 2016). Such information may arise not only by the consumers' past experiences (Mueller, Osidacz, Francis and Lockshin, 2010) or knowledge about the product itself or the sector (Dodd, Laverie, Wilcox and Duhan, 2005;King, Johnson, Bastian, Osidacz and Francis, 2012), but also by product related factors (Barber and Almanza, 2006;Mueller, Lockshin, Saltman, et al, 2010;Sáenz-Navajas, Campo, Sutan, Ballester and Valentin, 2013;Veale, 2008) and recommendations from reliable sources (Dodd et al, 2005;Loureiro and Cunha, 2017). Bloch (1995) highlights how a product's form and design can lead to positive responses such as an immediate liking or desiring of the product.…”
Section: Perceived Quality Of Winementioning
confidence: 99%
“…However, the discussion regarding the conceptualisation and the measurement of relationship quality is still unsolved (Cheng et al, 2008;Lo and Im, 2014). Many authors have suggested a few definitions, but there is no agreement about which is the most appropriate, and the constructs for its measurement have significantly increased (Loureiro and Cunha, 2017). Thus, some authors suggest that relationship quality lacks both formal definition as well as consensus about what dimensions involve.…”
Section: Introductionmentioning
confidence: 99%